Impacto del cultivo de soja sobre tierras desmontadas en la provincia del Chaco - Lopez, Astor Emilio; Roldan, Maria Florencia; Zurita, Juan Jose; Brest, Elías Francisco; Giménez, Laura Itatí; Montico, Sergio (Asociación Argentina Ciencia del Suelo (AACS), 2020)
Póster